Growth Performance, Histological Structure of Duodenum and Pectoralis Muscle of Kampung Chickens After Administration of Antibiotic Growth Promoter - Hendry Trisakti Saragih; Suci Aulia Ratu Fajrin; Sovia Nur Janah; Ria Oktafianti; Elgio Venanda Ginting; Anisa Fatwa; Stephanus Ardi Dimarjati; Indra Lesmana (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
This study aimed to know the effect of AGP on growth performance, duodenal histological structure and pectoralis muscle of Kampung chicken. This research was conducted by designing 3 groups with each group consisting of 20-day old chicks (DOC) of Kampung chickens. The control group was given basal feed without AGP bacitracin, group 2 was treated with 0.125 g of bacitracin /kg of basal feed and group 3 was treated with 0.25 g bacitracin/kg of basal feed until 12 days old. The parameters observed were chicken body weight on days posthatch, 3, 5, 7, 9, and 12, morphometry, visceral organ weight, duodenal organ morphology and muscle performance of Pectoralis thoracicus at 12 days old. Data analysis used one way ANOVA test followed by Tukey test with significance of P≤ 0,05. The result showed that the morphology of the doudenum and the myofiber area of group 3 indicated significant differences compared to the control group. The conclusion of this study revealed that administration of AGP bacitracin with 0.25 g/ kg dose of basal feed may increase the growth performance of Kampung chicken.